Nutrition and acute schistosomiasis - Eridan M. Coutinho; Haroldo S. Ferreira; Lucia P. C. G. de Freitas; Marlene R. Silva; Claudia L. Cavalcanti; Maria de Jesus Samico (Memorias do Instituto Oswaldo Cruz, 1992)
In northeast Brazil, nutritional deficiency diseases and schistosomiasis mansoni overlap. An experimental model, wich reproduces the marasmatic clinical form of protein-energy malnutrition, was developed in this laboratory to study these interactions. Albino Swiss mice were fed with a food association ingested usually by human populations in northeast Brazil. This diet (Regional Basic Diet - RBD) has negative effects on the growth, food intake and protein utilization in infected mice (acute phase of murine schistosomiasis). Nitrogen balance studies have also shown that infection with Schistosoma mansoni has apparently no effect on protein intestinal absorption in well nourished mice. However, the lowest absorption ratios have been detected among RBD - fed infected animals, suggesting that suprerimposed schistosome infection aggravated the nutritional status of the undernourished host. The serum proteins electrophoretic pattern, as far as albumins are concerned, is quite similar for non-infected undernourished and infected well-fed animals. So, the significance of albumins as a biochemical indicator of the nutritional status of human populations residing in endemic foci of Manson's schistosomiasis, is discussable.